Modernitas dan Konteks Sosial dalam Penafsiran Al-Qur’an: Studi Komparatif QS. Al-Baqarah [2]: 256 dalam Tafsir Al-Manār dan Tafsir Al-Azhar - Moh Firdaus HN (Universitas Islam Negeri Sunan Kalijaga, 2025)
This article aims to comparatively examine the interpretation of QS. Al-Baqarah [2]:256 in two influential modern tafsir works: Tafsir al-Manār and Tafsir al-Azhar. The analysis focuses on their methodological approaches, social contexts, and discursive orientations. Employing a comparative-hermeneutic framework and contextual discourse analysis, this study finds that although both interpretations reject religious coercion, they exhibit significantly different interpretive styles and argumentative strategies. Al-Manār employs a rational-philosophical and apologetic approach, clearly targeting intellectuals, reformists, and a global readership amid the 20th-century Islamic reform movement in Egypt. In contrast, al-Azhar emphasizes psychological, contextual, and populist dimensions, aiming at the general public, students, and local Indonesian figures in the post-colonial era. These findings underscore that tafsir is not merely the result of textual understanding but also a dynamic expression of the interplay between text, interpreter, and socio-cultural context. This study offers a valuable contribution to strengthening religious moderation through Qur’anic interpretation studies.